Pengaruh Pemberian Rebusan Daun Kelor Terhadap Produksi Asi: Literatur Review - Auliah Rahmi Latif; Risna Damayanti (Universitas Pahlawan Tuanku Tambusai, 2024)
As part of traditional medicine in various cultures, moringa leaves are often consumed in the form of a decoction to increase breast milk production, because moringa leaves have the ability to act as galactogues The purpose of this study is to identify the effect of moringa leaf decoction on breast milk production based on existing scientific evidence. The method used in this study is a literature review (Literature revew). The results in this study were obtained from 5 appropriate and analyzed literature, from the five literatures showing the effect of moringa leaf decoction on increasing breast milk production. Giving moringa leaf decoction can be an alternative in an effort to increase breast milk production so that exclusive breastfeeding can be applied.